Aplicação de inteligência computacional para navegação autônoma na robótica educacional - Lopes Neto, Alfredo Felipe (Universidade Federal Rural do Semi-Árido, 2020)
This article describes the implementation of a neural network with the purpose of navigating a robot avoiding obstacles, discriminating two versions, a simulation developed using the Python language and a robot prototype using LEGO pieces and its own language, the EV3-G.
Keywords: Inteligência computacional; Robótica; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO